Conceptual model and flow numerical simulation of aquifer contaminated by chlorinated solvents in rho (mi) - bozzano, francesca; petitta, marco; del bon, andrea; nardoni, fabrizio; pacioni, ava (Italian journal of engineering geology and environment, 2007)
The geological and hydrogeological characterization of a multilayer aquifer contaminated by organochlorinated compounds has been carried out in the industrial area of Rho (Milan, Italy). The hydrogeological setting is characterized by the presence of several aquifers overlying each other, separated by silty-clayey levels, whose presence and thickness tends to increase with depth. The “first aquifer”, 35 m thick, is separated by a clayey level, located at 5-9 m below ground level varying in thickness between 0.5 and 2 m, from a perched aquifer of local interest, indicated as “shallow aquifer”. Groundwater flows towards SSE in both shallow and deeper aquifer, with a mean 0.6% hydraulic gradient, showing highest values (+2 m) of the hydraulic head of the shallow aquifer, allowing possible seep- age from the shallow aquifer to the deeper one, taking into account the small thickness of the aquitard. Geological, hydrogeological and hydrogeochemical data have been included in a GIS and they have been used to interpolate geometry, thickness and piezometric surface of the shallow aquifer, of the aquitard and of the first aquifer. By scarcity of the experimental data, hydraulic coefficient evaluation has been integrated starting from grain size classes on single vertical boreholes. Space distribution of k has been derived by geostatistical tools, after validation of k classes referring to available investigation data. Two groundwater flow mathematical models have been developed for the multilayer aquifer at different scales; a large scale model (LSM) and a fine scale one (FSM). After calibration and validation, the LSM sufficiently agrees with experimental data, offering the possibility to simulate regional flowpaths, both in shallow and first aquifer. Shallow aquifer heterogeneity appears significant in groundwater flow influence, allowing simulation of local flowpaths differently oriented from main groundwater flow direction.Heterogeneities in the first aquifer have not been reproduced in numerical models, assigning an average value of hydraulic conductivity to the layer, considered as an homogeneous aquifer for groundwater flow simulation. At the FSM scale, a deeper characterization of the first aquifer it seems necessary, because simple uniform values of k cannot correctly simulate local water table variations and real flowpath directions. It can be inferred that this FSM can be used only to simulate shallow aquifer and seepage towards the first aquifer. Meanwhile, the FSM model cannot be used to assess final fate of the contaminant in the first aquifer. Models support field data about the seepage from the shallow to the first aquifer, of both groundwater and dissolved contaminants, showing vertical transfer by particle tracking through the thinaquitard, which can explain high contaminant concentrations found in the first aquifer.